Motivasi Menjadi Seorang Sukarelawan Pengatur Lalulintas (Supeltas) - Khoirina, Cony; , Rini Lestari,S.Psi, M.Si (2016)
The phenomenon of traffic jams that occurred at different spots in Surakarta were vulnerable due to the imbalance between the number of mass public transport with private transport resulted in some people voluntarily smooth the traffic which was well-known as Sukarelawan lalu lintas or Supeltas. The emergence of several traffic-control volunteers who voluntarily help to smooth the traffic existed since 2006 after officially recognized by Satlantas Kota Surakarta. This study aims to find their motivation to become a Supeltas, where traffic-control volunteers (Supeltas) only received revenue from passing-by drivers but remain steadfast. The research was conducted on five informants who worked in Surakarta and already have a official membership card from Satlantas Surakarta. The method used in this research is qualitative method with phenomenological approach. Informations were gathered through interviews and observations, while the use analysis use content analysis. Based on the researched it revealed that the motivation to be a traffic-control volunteers are the desire or urge wholeheartedly to help smooth the traffic, concerned with congestion up to the accident that occurred at some vulnerable spots, desire to worship by helping people, and desire to devote themselves to the society. Keywords: Motivation, Traffic-control volunteers, Supeltas.